Iceland : 2007 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that boom in private consumption in Iceland was facilitated by easing household credit conditions, tax cuts, rapidly rising housing and equity wealth, and an appreciating real exchange rate. As a result, the output gap peaked at over 5 percent in 2005, declining only modestly in 2006. Record current account deficits and credit downgrades early in 2007 caused little market disruption, in part reflecting a healthy financial sector. The exchange rate remained strong, and confidence in Icelandic banks stayed high.